The Zionist churches in Malawi : history, theology, anthropology - Strohbehn, Ulf (Mzuzu : Mzuni Press, 2016)
This book presents an African Christian movement full of vitality and creativity. The reader will meet believers who drink milk so that they may dream about angels, reports about funerals where the mourners dance with the coffin on their shoulders and church members who are ritually not allowed to fertilize their fields or wear neck ties. The author's unique insight into Malawi's Christian community addresses important issues in society. Why have 'Spirit Churches, ' including Pentecostalism, been so successful in Malawi? Why do some religious groups still refuse medical help, up to the point that children die of cholera? How did the independent churches deal with the colonial trauma? In this masterful portrait, Strohbehn takes the reader from industrial mine compounds to rural colonies, where churches have set up their own spiritual and political rule. He carefully dissects the fine lines between traditional notions and Christianity's influence. We find a spiritual portrait of the Ngoni people, a fascinating cultural analysis of dancing and an encounter with a unique style of preaching.
Bearings: the spiritual field -- Origins in exile: American roots, Ngoni Mfecane and Machona labour migration -- History: Zionism in Malawi 1922-2011 -- Identity: what constitutes Zionism -- Theology: salvation and the church -- Culture: two circles.
Includes bibliographical references (pages 489-524) and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Zionist churches (Africa) -- Doctrines; Zionist churches (Africa) -- Malawi; Malawi -- Church history; Christianity and culture -- Malawi; RELIGION -- Christianity -- Denominations; HISTORY / Africa / South / General; Christianity and culture; Zionist churches (Africa); Malawi; Electronic books; Electronic books; Church history